Market-Led Institutional Innovations for Farmers’ Inclusive Growth and Livelihood Security - R.N. Padaria, N.V. Kumbhare, Sujit Sarkar and V. Lenin, (Indian Journal of Extension Education, 2017)
The study aimed at analyzing some successful models of institutional arrangements in India, where-in linking tovalue chains and markets facilitated inclusive growth of farmers. The grain festival could enhance the income offarmers, while helped consumers by way of ensuring savings as well as quality produce at competitive rates.Linking the linseed growers’ association to value chain helped the member’s secure additional benefits of $10.30per quintal of produce. Similarly, operations through SHGs and federations, helped landless tribal women adoptsericulture on leased land to ensure livelihood security. Membership of growers’ association (MAHAGRAPE)helped the grape growers securean additional profit of $3958 per hectare through adoption of proper production;harvesting and post-harvest management practices, and savings on transaction costs. Factor analysis revealedfinancial management, incentives and welfare measures for members, trust among the members, democratic style ofleadership, transparency in dealings, and identity of the organization as the major facilitating factors for sustainabilityof farmers’ organizations. The suggestive measures for effective and sustainable functioning of farmers’ producer’sorganizations and growth include access to land and capital for developing processing and ware house units,provision of seed money, easy access to credit, capacity building facilities, and tax exemption.